Best approximation of reproducing kernels of spaces of analytic functions - Savchuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We obtain exact values for the best approximation of a reproducing kernel of a system of p-Faber polynomials by functions of the Hardy space H q, p -1 + q -1 = 1 and a Szegö reproducing kernel of the space E 2(Ω) in a simply connected domain Ω with rectifiable boundary.